RETINOL bINDING PROTEIN AS A MARKER OF CARDIOVASCULAR RISK IN ARTERIAL HYPERTENSION AND ObESITY - Yu. A. Vasyuk; I. A. Sadulaeva; E. N. Yushchuk; O. S. Trofimenko; S. V. Ivanova (Российский кардиологический журнал, 2018)
Aim.  To assess the influence of retinol-binding protein synthetized by adipose tissue, on clinical course and prognosis of arterial hypertension (AH).Material and methods. Totally, 168 patients included, with AH of 1-3 grade. Study protocol included general clinical investigation (at inclusion, in 1, 4 and 9 months) with analysis of complaints, anamnesis, physical examination, additional laboratory and instrumental methods. In 78 patients among the included, the level of retinolbinding protein RBP4 was measured in blood serum.Results. Increased level of RBP4 correlated significantly with the age, body mass index, duration of AH, raised level of uric acid, pulse wave velocity signs, endogenic nitrite. Only in the group with raised RBP4 there was stroke anamnesis noted, and obesity of III grade. Dynamics of the level of RBP4 during 9 months treatment, depending on cardiometabolic risk, showed some specifics: at inclusion, in the group with high cardiometabolic risk there was significantly increased RBP4 comparing to the groups of patients with low and moderate cardiometabolic risk.Conclusion. Increased level of retinol-binding protein is associated with higher cardiometabolic risk and adverse prognosis.